Evolusi Dan Kemajuan Industri Otomotif Melalui Ajang Balapan Dan Pameran Di Era Teknologi Novel The Mechanics Karya Annisa Lim - Odi Pradinata; Dicky Hidayatullah; Eva Dwi Kurniawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this journal's research is to discuss the development and progress of the automobile industry in the face of technological change, especially through the important role of racing events and exhibitions in Anisa Lim's novel The Mechanics. A positive path for racing events, arousing competitive spirit and promoting improved vehicle performance. We will promote the development of the latest technology. In addition, automobile trade fairs are considered an important platform for the presentation of consumers and industry representatives. A detailed analysis of the role of these events is expected to provide deeper insights into the dynamics of the automotive industry in the current technological era and provide positive prospects for future development directions. Masu. Quantitative methods are used in this study. The analysis process also considered variable determination and measurement. Identify the variables you want to investigate. B. Improving vehicle performance, sales, or adoption of automotive technology. Quantitative methods are about testing hypotheses against existing theory. Therefore, this research tends to be objective and not deep. Through this study, we will provide deep insights into technology, automobiles, evolution, and progress, in order to expand our experience and knowledge about the innovation process of new jobs, especially in the technology field